2008
DOI: 10.1091/mbc.e08-04-0433
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 Regulates Directional Cell Migration by Acting on Gβγ at the Interface with Its Effectors PLCβ and PI3Kγ

Abstract: Migration of cells up the chemoattractant gradients is mediated by the binding of chemoattractants to G protein-coupled receptors and activation of a network of coordinated excitatory and inhibitory signals. Although the excitatory process has been well studied, the molecular nature of the inhibitory signals remains largely elusive. Here we report that the receptor for activated C kinase 1 (RACK1), a novel binding protein of heterotrimeric G protein ␤␥ (G␤␥) subunits, acts as a negative regulator of directed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 57 publications
(98 reference statements)
4
69
0
Order By: Relevance
“…Thus, TRPV2 activation and MEK1/2 phosphorylation are part of one and the same intracellular pathway that mediates OXT-induced anxiolysis. This anxiolytic pathway likely starts with OXTR-induced G protein β/γ-subunit activation, which permits binding of PI3K to the G protein (Chen et al, 2008). Consequently, PI3K is activated and incorporates TRPV2 channels in the plasma membrane, leading to Ca 2+ influx and MEK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TRPV2 activation and MEK1/2 phosphorylation are part of one and the same intracellular pathway that mediates OXT-induced anxiolysis. This anxiolytic pathway likely starts with OXTR-induced G protein β/γ-subunit activation, which permits binding of PI3K to the G protein (Chen et al, 2008). Consequently, PI3K is activated and incorporates TRPV2 channels in the plasma membrane, leading to Ca 2+ influx and MEK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture-Jurkat T cells stably expressing FLAG-WDR26 and the HL60 cell line (ATCC) were grown in RPMI 1640 medium (Invitrogen) containing 10% fetal bovine serum (FBS) as described previously (3,16). HEK293 cells (ATCC) were maintained in DMEM (Invitrogen) supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they directly interact with and modulate the activity of a long list of proteins including receptors, ion channels, and enzymes such as PLC, 2 phosphoinositide 3-kinases (PI3Ks), and G protein-coupled receptor kinase 2. Through these downstream targets, G␤␥ regulates diverse functions including immune and tumor cell migration (3)(4)(5), yeast cell mating (6), and heart rate (7).…”
mentioning
confidence: 99%
“…Consistent with this hypothesis, co-immunoprecipitation studies showed that upon chemoattractant stimulation, WDR26 rapidly forms a complex with Gβγ (within five minutes of stimulation), whereas the interaction of RACK1 with Gβγ was delayed, occurring nearly thirty minutes after stimulation. 31,32 Moreover, downregulation of WDR26 blocked the interaction of RACK1 with Gβγ and its ability to negatively regulate Gβγ-mediated cell migration, indicating that RACK1 functions downstream of WDR26. 32 Despite our initial findings on the importance of WDR26 and RACK1 in regulating leukocyte migration, a number of key questions remain unanswered.…”
mentioning
confidence: 97%
“…[29][30][31] Downregulation of RACK1 by siRNAs enhanced SDF1α-and fMLP-stimulated chemotaxis of Jurkat T cells and differentiated HL60 cells, whereas overexpression of RACK1 leading edge via F-actin polymerization. 14 Additionally, G12/13-mediated RhoA activation antagonizes Gβγ-mediated PI3Kγ activation at the posterior of neutrophils, reinforcing PI3K activity at the leading edge.…”
mentioning
confidence: 99%